PENGARUH KINERJA PENGELOLAAN KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI, PENGANGGURAN DAN KEMISKINAN DI KOTA DEPOK - Suryanta Suryanta (Cakrawala Management Business Journal, 2019)
This study aims to analyze whether the performance of regional financial management influences economic growth in Depok City, analyzes whether the performance of regional financial management influences unemployment in Depok City, and analyzes whether the performance of regional financial management affects poverty in Depok City with the 2006 study period- 2015 The analysis method used is quantitative descriptive analysis and simple linear regression statistical analysis. Based on the results of hypothesis testing it can be proven that the performance of regional financial management (independence ratio) has a positive and significant effect on economic growth, this can be seen from the value of sig. 0.046 <0.05 with a regression coefficient of 1.883. Then the performance of regional financial management has a negative and significant effect on unemployment, this can be seen from the value of sig. 0.030 <0.05 with a regression coefficient of -6.864. But the performance of regional financial management has no significant effect on poverty, this can be seen from the sig. 0.065> 0.05 with a regression coefficient of -0.512. This can be due to the still high income gap in the community, so that the increasing regional income has not been able to significantly reduce poverty in Depok.